Electrospun nickel nanoparticles@poly(vinylidene fluoride-hexafluoropropylene) nanofibers as effective and reusable catalyst for H2 generation from sodium borohydride - Abdullah M. Al-Enizi; M.M. El-Halwany; Shoyebmohamad F. Shaikh; Bidhan Pandit; Ayman Yousef (Arabian Journal of Chemistry, 2022)
Nickel nanoparticles (Ni NPs) supported on Poly(vinylidene fluoride-co-hexafluoropropylene) nanofibers (PVDF-HFP NFs) were successfully synthesized through electrospinning and in-situ reduction of Ni2+ salts into the surface of PVDF-HFP NFs to form metallic Ni NPs@PVDF-HFP NFs. Different percentages of nickel acetate tetrahydrate (NiAc) (10 %, 20 %, 30 %, 40 % wt.) based PVDF-HFP. The formation of tiny metallic Ni NPs @PVDF-HFP membrane NFs was demonstrated using standard physiochemical techniques. Nanofibers membranes have demonstrated good catalytic activity in H2 production from sodium borohydride (NaBH4). The sample composed of 40 %wt Ni showed the highest catalytic activity compared to the other formulations. Whereas 103 mL of H2, from the hydrolysis of 1.34 mmol NaBH4, was produced using 40 wt% NiAc compared to 68 mL, 81 mL, and 93 mL for 10 wt%, 20 wt%, and 30 wt% NiAc, respectively, in 60 min at 25 °C. The hydrogen generation has been enhanced with an increase in the Nanofibers membrane amount and reaction temperature. The latter results in a low activation energy (23.52 kJ mol−1). The kinetics study revealed that the reaction was pseudo-first-order in sodium borohydride concentration and catalyst amount. Furthermore, the catalyst exhibits satisfactory stability in the hydrolysis process for ten cycles. Because of its easy recyclability, the introduced catalyst has a wide range of potential applications in the generation of H2 from sodium borohydride hydrolysis.